Generation of neuronal cells from human peripheral blood mononuclear cells - Horschitz, Sandra; Meyer-Lindenberg, Andreas; Schloss, Patrick (Neuroreport, 2010)
We have examined the potency of two methods for the neuronal differentiation of embryonic stem cells on the generation of neuronal cells from human blood cells. A mixture of mononuclear cells from peripheral blood cells expressing monocytic, hematopoietic, and mesenchymal cell surface markers were exposed to all-trans retinoic acid, epidermal growth factor, and basic fibroblast growth factor (method A), or epidermal growth factor, fibroblast growth factor 8b, sonic hedgehog and ascorbic acid (method B). Both methods led to the generation of neuronal cells as judged by changes in morphology and the expression of the neuronal markers microtubule-associated protein type 2, tau, and β-tubulin III. Differentiation according to method B favoured the development of neurons also expressing the dopamine transporter.